Actualization Of Mental Health And Self-Reliance Through Health-Based Education Management - Achalu, Dorathy; Asanga, Dorothy (Advances in Social Sciences Research Journal, 2018)
The study is aimed at assessing the actualization of mental health and self-reliance through health based education management among public secondary school students in Akwa Ibom State, Nigeria. Three research questions and three research hypothesis were postulated to guide the study. The population of the study comprised all the 233 public secondary schools in Akwa Ibom State. A sample of 72 physical and health education teachers selected from 45 randomly selected secondary schools in the three Senatorial District of the state. A self developed questionnaire was used as the primary instrument for data collection for the study, and Pearson Product Moment Correlation and simple regression analysis were used to test the hypotheses. The finding revealed a significant relationship between health based education management and the actualization of based programmes and significant influence on mental health was self-reliance among secondary school students while that of the Nigeria education system was statistically insignificant. It was recommended among others that, health based education programmes should be incorporated into the secondary education system in Nigeria to enhance good mental health of the students and skill for self-reliance.